Ryzykowne zachowania seksualne bezdomnych kobiet - Szluz, Beata (Univerzita Pavla Jozefa Šafárika v Košiciach, 2014)
In the article are the deliberations concerning the risk sexual behaviors of homeless women. This article was written based on i ts own broader study, which was conducted in 2009 among 52 homeless women in the Po dkarpackie voivodship. The test subjects were selected in terms of age, place of re sidence during the conducted research, and their occasional or permanent residence in a shelte r. The biographical method, and the narrative interview technique, a special form of fr ee or in-depth interview, were used.

W artykule zawarto rozwa ż ania dotycz ą ce ryzykownych zachowa ń seksualnych bezdomnych kobiet. Artykuł został napisany w oparci u o własne, szersze badania, które zostały przeprowadzone w 2009 roku w ś ród 52 bezdomnych kobiet w województwie podkarpackim. Respondentki zostały wybrane ze wzgl ę du na wiek, miejsce zamieszkania podczas prowadzonych bada ń , ich okazjonalne lub stałe przebywanie w schronisk u. Zastosowano metod ę biograficzn ą i technik ę wywiadu narracyjnego.
Keywords: homelessness; homeless women; risky sexual behaviors; sexual activity; bezdomność; bezdomność kobiet; ryzykowne zachowania seksualne; aktywność seksualna